European standards on the right to privacy - Tokuzlu, Lami Bertan (My University, 2000)
Privacy is a fundamental human right which has been recognised in most of the international human rights instruments as a right that protects individual from intrusions against his intimate zone, information and actions in the context of 'private life', 'family', 'home', 'correspondence' and 'reputation' This study focuses on both theoretical and positive law aspects of the European standards on the right to privacy. National laws are not addressed unless indispensable for analysing international norms. The first section of the study that carries the heading 'Origins and the Value of Privacy and Problems of Definition' consists of three parts. The first part is devoted to the analysis of different theories on the origins of the right to privacy with a sociology/ anthropology and legal history perspective. The second part contains theoretical discussions on the value of the right to privacy. The third part is devoted to the definition of the right and the problems encountered in this regard. As a conclusion, a model of definition is proposed which is applied for identifying the common parameters of definition of the right in European positive law. The second section of the study carries the heading Certain Aspects of the Right to Privacy. This section contains a general survey on certain aspects of the right to privacy with particular emphasis on the case-law. The aspects covered by this section are 'respect for home', 'telephone tapping' and 'sexual choice'. Other aspects such as 'personal data', 'family life' are not covered by this study.

Özel yaşamın gizliliği hakkı birçok uluslararası insan hakları belgesinde düzenlenmiş, kişiyi mahrem alanına, bilgilerine ve hareketlerine müdahalelere karşı 'özel yaşam', 'aile', 'ev', 'iletişim' ve 'haysiyet' kavramları çerçevesinde koruyan bir haktır. Bu çalışma özel yaşamın gizliliği konusundaki Avrupa standartlarını teorik ve pozitif hukuk boyutları ile incelemektedir. Ulusal düzenlemelere ise uluslararası normların analizi için kaçınılmaz olmadıkça değinilmemiştir. Çalışmanın Hakkın Orijini ve Değeri ve Tanım Problemi başlığını taşıyan birinci kısmı üç alt bölümden oluşmaktadır. hakkın orijinini sosyal-antropoloji ve hukuk tarihi perspektifi ile incelemektedir. İkinci bölüm ise hakkın değerine ilişkin teorilere ayrılmıştır. Üçüncü bölümde hakkın tanımına ilişkin teoriler ve bu bağlamda karşılaşılan güçlükler irdelenmiştir. Burada bir tanım modeli ortaya konulmuş ve daha sonra Avrupa pozitif hukukunun gelişimi sonucunda ortaya çıkan hakkın tanıma ilişkin ortak parametreler bu model çerçevesinde tespit edilmiştir. Çalışmanın ikinci kısmı Hakkın Bazı Boyutları başlığını taşımaktadır. Bu kısımda hakkın bazı boyutları mahkeme içtihatları ışığında değerlendirilmiştir. Bunlar evin korunması, telefon dinleme ve seksüel tercihlerdir. Diğer yandan hakkın kişisel bilgilerin korunması ve aile yaşamı gibi tek başına etraflı bir araştırmanın konusu olabilecek ve kendine özgü düzenlemeleri bulunan boyutları çalışma kapsamı dışında bırakılmıştır.
Keywords: Özel yaşamın gizliliği hakkı; Şahıs hukuku